Rancangan Sistem Informasi Akuntansi Keuangan Masjid Berbasis Google Spreadsheet Sesuai Isak 335 - Fahmi, Muhammad; Tezar, Muhammad (EKALAYA : Jurnal Ekonomi Akuntansi, 2025)
This study aims to design a mosque financial accounting information system based on Google Spreadsheet in accordance with ISAK 35 guidelines. The research employs an experimental method, where the system is designed, implemented, and tested to evaluate its effectiveness in managing mosque financial reports. Google Spreadsheet is chosen as the primary platform due to its ease of use, accessibility, and ability to automate financial transaction recording. This application enables systematic financial report processing by inputting journal transactions and initial balances accurately. The research findings indicate that the Google Spreadsheet-based system can serve as an alternative for mosque financial reporting, similar to other accounting applications such as Accurate and Zahir Accounting. However, the developed system is still limited to small-scale implementations and requires further development to accommodate larger-scale usage with more complex features. Therefore, this study recommends further enhancements by integrating automation and data validation features to improve accuracy and efficiency in mosque financial management.